2000
DOI: 10.1366/0003702001949258
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Noninvasive in vivo Blood Hematocrit Measurement Using NIR Reflectance Spectroscopy and Partial Least-Squares Regression

Abstract: Hematocrit (Hct), the volume percent of red cells in blood, is monitored routinely for blood donors, surgical patients, and trauma victims and requires blood to be removed from the patient. An accurate, noninvasive method for directly measuring hematocrit on patients is desired for these applications. The feasibility of noninvasive hematocrit measurement by using near-infrared (NIR) spectroscopy and partial least-squares (PLS) techniques was investigated, and methods of in vivo calibration were examined. Twent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 10 publications
1
28
0
1
Order By: Relevance
“…With PLS, the sensitivity and specificity were 86% and 91%, while the discrete region model yielded 57% and 100%, respectively, indicating the importance of exploring these models further. While most of the studies described here exhibited good in vivo correlations of optical or acoustic parameters to total Hb and hematocrit, they typically are only useful for measurements of arterial saturations [4,5,8], require sophisticated algorithms [8,9,14] or have shown significant inter-patient variability due to skin pigmentation in the cases where measurements were made through the intact skin [12,13]. This presents an opportunity to explore new approaches that can address all three of these issues.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…With PLS, the sensitivity and specificity were 86% and 91%, while the discrete region model yielded 57% and 100%, respectively, indicating the importance of exploring these models further. While most of the studies described here exhibited good in vivo correlations of optical or acoustic parameters to total Hb and hematocrit, they typically are only useful for measurements of arterial saturations [4,5,8], require sophisticated algorithms [8,9,14] or have shown significant inter-patient variability due to skin pigmentation in the cases where measurements were made through the intact skin [12,13]. This presents an opportunity to explore new approaches that can address all three of these issues.…”
Section: Introductionmentioning
confidence: 94%
“…In that study, the one anemic donor out of 19 donors was identified, but the estimates of Hb were affected by the skin pigmentation of the calibration population. In a different study utilizing NIR reflectance measurements from the forearm of cardiac bypass patients with hematocrit ranging from 14.3 to 44.2%, a correlation coefficient of r=0.71 was achieved when compared to arterial Hb [13]. However, skin pigmentation was again found to be a largely contributing factor to the predictive ability of this technique.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al reported on the utility of a similar visible/NIR diffuse reflectance spectroscopy technique (33 ). A fiber optic probe was attached against the patient's forearm (34 ), and NIR reflectance spectra were collected during cardiopulmonary bypass surgery.…”
Section: Reflectance Spectroscopymentioning
confidence: 99%
“…The data presented suggest the feasibility of measuring Hb and Hct noninvasively using steady-state reflectance measurements in a limited population of different skin colors. This type of steadystate determination of Hb and Hct, as well as the cardiac-pulse-based signal processing techniques, has been described in the literature (5)(6)(7)(8). The steady-state methods have a potential advantage for the determination of analytes in weak cardiac pulse situations.…”
Section: Noninvasive (Ni)mentioning
confidence: 99%